INNOVATIVE TECHNOLOGIES IN THE EDUCATIONAL PROCESS (Conference Zone, 2022)
Innovative technologies in education allow you to regulate learning , to direct it in the right direction . People were always afraid of everuthing unknown and new , they had a negative attitude to any changes.